2014
DOI: 10.1111/ejn.12783
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptors preferentially regulate the development of light responses of the inner retina

Abstract: Retinal light responsiveness measured via electroretinography undergoes developmental modulation and is thought to be critically regulated by both visual experience and dopamine. The primary goal of this study is to determine whether the dopamine D2 receptor regulates the visual experience-dependent functional development of the retina. Accordingly, we recorded electroretinograms from wild type mice and mice with a genetic deletion of the gene that encodes the dopamine D2 receptor raised under normal cyclic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 87 publications
(213 reference statements)
3
13
0
Order By: Relevance
“…and cats 42 and by genetic KO in mice, 43,44 but is opposite that which is seen in rabbits. 45 We also found that suppression of the b-wave and summed OP amplitudes by the D1R antagonist SCH39166 resembled the ERG phenotype of the D1R-KO mice.…”
Section: D1r-dependent Mechanism Of Apomorphine In Myopiamentioning
confidence: 83%
“…and cats 42 and by genetic KO in mice, 43,44 but is opposite that which is seen in rabbits. 45 We also found that suppression of the b-wave and summed OP amplitudes by the D1R antagonist SCH39166 resembled the ERG phenotype of the D1R-KO mice.…”
Section: D1r-dependent Mechanism Of Apomorphine In Myopiamentioning
confidence: 83%
“…Smaller a-wave deflections in young mice (P8-P10) were expected, considering the low expression profiles of a number of critical players in the phototransduction cascade [(33) and for a review, see Swaroop, Kim (40)]. Two ERG studies in the anesthetized P13 mouse pup found an approximately 50μV a-wave response to a bright white light stimulus, which would have activated, both m-opsin cones and rods (17, 19). …”
Section: Discussionmentioning
confidence: 99%
“…Dopamine released in the retina solely by dopaminergic amacrine cells in the light [23][24][25] plays a key role in visual processing, synaptic formation, synaptic transmission, and light adaptation [26,27]. Dopamine D1 receptors are located on horizontal cells, bipolar cells, amacrine cells (ACs) and RGCs [28,29]; dopamine D2 receptors are expressed by photoreceptors, ACs and RGCs [27,[30][31][32]. Dopamine is arguably involved in visual experience-modulated eye growth [33,34].…”
Section: Introductionmentioning
confidence: 99%